Metode Live Memory Acquisition untuk Pencarian Artefak Digital Perangkat Memori Laptop Berdasarkan Simulasi Kasus Kejahatan Siber - M. Ainul Yaqin; Triawan Adi Cahyanto; Nur Qadariyah Fitriyah (Puslitbang Sinergis Asa Professional, 2021)
Information technology's hardware and software are constantly evolving. The rise in cybercrime cases is consistent with this trend. While operating systems can be hacked, personal data can be stolen and encrypted, making it impossible for users to access the information. Cybercriminals are using social media data to target personal information currently. Users' usernames, passwords, and other personal information can be stored in a device's memory, as well as browser cookies. Pre-analysis, analysis, and post-analysis are the three stages of the research process.